2013
DOI: 10.1080/15287394.2013.757256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gamma Radiation on Raspberries: Safety and Quality Issues

Abstract: There is an ever-increasing global demand from consumers for high-quality foods with major emphasis placed on quality and safety attributes. One of the main demands that consumers display is for minimally processed, high-nutrition/low-energy natural foods with no or minimal chemical preservatives. The nutritional value of raspberry fruit is widely recognized. In particular, red raspberries are known to demonstrate a strong antioxidant capacity that might prove beneficial to human health by preventing free radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 45 publications
4
31
0
Order By: Relevance
“…In order to estimate specific changes of nutritional quality of raspberries, we evaluated the amount of ascorbic acid, total phenolic compounds, soluble solids, DPPH and flavonoids anthocyanins (Table 3). The raspberry fruit firmness depends on the variety, berry maturity, environmental conditions, processing, transportation and others factors (Verde et al, 2013). It was difficult to evaluate the influence of treatments on the disease incidence because raspberries are very fast perishable fruits (data are not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to estimate specific changes of nutritional quality of raspberries, we evaluated the amount of ascorbic acid, total phenolic compounds, soluble solids, DPPH and flavonoids anthocyanins (Table 3). The raspberry fruit firmness depends on the variety, berry maturity, environmental conditions, processing, transportation and others factors (Verde et al, 2013). It was difficult to evaluate the influence of treatments on the disease incidence because raspberries are very fast perishable fruits (data are not shown).…”
Section: Resultsmentioning
confidence: 99%
“…During storage, they lose firmness and change colour. The nutrition value of raspberries is very high, phenolic compounds are a major group of phytochemicals found in berries (Verde et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…An irradiation dosage of 1 kGy is permitted for fresh foods for inhibition of growth and maturation (FDA, 2008); at this dose, there was virtually no reduction in HAV titers on strawberries (Bidawid et al, 2000). Similarly, raspberries treated with 1.5 kGy gamma radiation reduced microbial load, but with effects on firmness, phenolic content, and antioxidant capacity during storage (Cabo Verde et al, 2013). Electron-beam irradiation of strawberries at doses of 1 and 2 kGy provided shelf-life extension of two and four days, respectively, although a decrease in firmness and increase in off-flavors were reported during storage of strawberries (Yu et al, 1995).…”
Section: Contamination Reduction Strategiesmentioning
confidence: 99%
“…Electron-beam irradiation of strawberries at doses of 1 and 2 kGy provided shelf-life extension of two and four days, respectively, although a decrease in firmness and increase in off-flavors were reported during storage of strawberries (Yu et al, 1995). Similarly, raspberries treated with 1.5 kGy gamma radiation reduced microbial load, but with effects on firmness, phenolic content, and antioxidant capacity during storage (Cabo Verde et al, 2013). Studies on the qualities of various types of blueberries receiving doses above 1 kGy reported decreases in ascorbic acid content (Moreno et al, 2008) and decreases in berry firmness Miller et al, 1994), but the berries were not necessarily deemed unacceptable.…”
Section: Contamination Reduction Strategiesmentioning
confidence: 99%